The Strategic Measures towards a Sustainable Competitive Advantage of the Restaurant Industry in Malaysia - Yip, Poh Yoke (2008)
The Food and Beverage (F&B) industry is a necessity industry to all nations in the world. The development of the restaurant have been increasing tremendously every year. The growth is clearly seen with many unique restaurants caming into existence as compared with a few decades ago. The reason are due to the low barrier of entry and low investment to establish restaurants have caused an increase in the number of restaurants both local and international offering a diverse variety of food into Malaysia. Malaysia’s main national cuisines are Malay, Chinese and Indian. However, due to the growth in the industry, there are many more international cuisines offered in Malaysia i.e. Western, Mediterranean, Middle East, Italian, Korean, Japanese among others. This has caused the industry to become so fragmented that many restaurants are unable to sustain themselves.Many restaurants have closed down. Sadly, many of the restaurateurs themselves cannot identify the reasons for their failure. Hence, the purpose of this study is to determine what are the strategic options that the restauraners can adopt to enable them to gain sustainable competitive advantage and also identified the reasons for their failure. This methodology adopted for this research is the case studies analysis methodology whereby primary method of data collection will be via face-toface interviews with the five restaurants in Kuala Lumpur disregarding ethnic background. The restaurants are Hakka Restaurants, Kelana Seafood Centre, Pik Wah Restaurant, Sri Paandi Restaurant and Devi’s Corner. The results of the research have proven many factors that are of intrinsic importance i.e. location, food quality, service quality, management skills, and human resource management. The results will also show that the restaurants must also be proficient in a number of factors in order have a sustainable competitive advantage.